124 When "the drugs don't work": think NMO!. Issue 3 (9th February 2012) - Ali, R; Jacob, A; Boggild, M
Abstract : We present a 21-year-old Caucasian female with antibody positive NMO, mis-diagnosed as MS for a period of 5 years. The diagnosis became evident only when bilateral severe optic neuritis occurred shortly after the introduction of Natalizumab. The patient presented in 2005, aged 15, with hemi-sensory symptoms and diplopia, resolving with methylprednisolone. MRI revealed a non-enhancing lesion in the left thalamus. CSF oligoclonal bands were absent. She experienced two further relapses characterised by hemi-sensory disturbance, diplopia and fatigue; again responding to steroids. MRI revealed a new brain stem lesion. A diagnosis of MS was made and she was treated with Interferon. Despite treatment she had two further relapses, brain-stem and spinal, with recovery. Treatment with Mitoxantrone followed by Glatiramer Acetate resulted in a 2-year remission. In 2010 she experienced three further sensory events (MRI spine normal). Treatment with Natalizumab was initiated. She experienced a further spinal event following the second infusion, resolving rapidly with steroids. In April 2011, after six infusions, she presented with rapid onset bilateral optic neuritis to NPL and was found to be Aquaporin-4 antibody positive. Treatment with steroids and plasma exchange resulted in full visual recovery over 6 weeks. She has now been commenced on Azathioprine. The clinical spectrum of NMO is expanding. In "MS" patients experiencing frequent relapses despite escalating therapy, even if attacks are non-disabling, NMO should be considered. Although n=1, this case suggests that Natalizumab may be ineffective in, or indeed exacerbate, NMO.